Behaviour of a capping layer reinforced with recycled tyres. Issue 3 (31st January 2019) - Sun, Qideng; Indraratna, Buddhima; Heitor, Ana
Abstract : In this paper, a sustainable approach for reducing lateral displacement in a track by increasing the confining pressure in the track substructure is demonstrated by placing a cellular rubber (tyre) membrane infilled with crushed ballast, as an alternative to a traditional capping layer of compacted granulates. Plate-load tests on a single tyre filled with gravel and subjected to a vertical load were carried out to investigate the interaction between tyre and gravel. A track model with tyre reinforcement was created to evaluate the performance of a tyre-reinforced capping layer under cyclic loading, and a numerical model was developed to determine the benefit that tyres would provide to railway substructure, especially when spent ballast is recycled as capping layer materials.